On the Effect of Gas Content in Centrifugal Pump Operations with Non-Newtonian Slurries - Nicola Zanini; Alessio Suman; Mattia Piovan; Michele Pinelli (Fluids)
Non-Newtonian fluids are widespread in industry, e.g., biomedical, food, and oil and gas, and their rheology plays a fundamental role in choosing the processing parameters. Centrifugal pumps are widely employed to ensure the displacement of a huge amount of fluids due to their robustness and reliability. Since the pump performance is usually provided by manufacturers only for water, the selection of a proper pump to handle non-Newtonian fluids may prove very tricky. On-field experiences in pump operations with non-Newtonian slurries report severe head and efficiency drops, especially in part-load operations, whose causes are still not fully understood. Several models are found in the literature to predict the performance of centrifugal pumps with this type of fluids, but a lack of reliability and generality emerges. In this work, an extensive experimental campaign is carried out with an on-purpose test bench to investigate the effect of non-Newtonian shear-thinning fluids on the performance of a small commercial centrifugal pump. A dedicated experimental campaign is conducted to study the causes of performance drops. The results allow to establish a relationship between head and efficiency drops with solid content in the mixture. Sudden performance drops and unstable operating points are detected in part-load operations and the most severe drops are detected with the higher kaolin content in the mixture. Performance drop investigation allows to ascribe performance drop to gas-locking phenomena. Finally, a critical analysis is proposed to relate the resulting performance with both fluids’ rheology and the gas fraction trapped in the fluid. The results here presented can be useful for future numerical validation and predicting performance models.